Kidney Disease and Youth Onset Type 2 Diabetes: Considerations for the General Practitioner - Allison B. Dart; Elizabeth A. Sellers; Heather J. Dean (International Journal of Pediatrics)
Youth onset type 2 diabetes (T2DM) continues to increase worldwide, concomitant with the rising obesity epidemic. There is evidence to suggest that youth with T2DM are affected by the same comorbidities and complications as adults diagnosed with T2DM. This review highlights specifically the kidney disease associated with youth onset T2DM, which is highly prevalent and associated with a high risk of end-stage kidney disease in early adulthood. A general understanding of this complex disease by primary care providers is critical, so that at-risk individuals are identified and managed early in the course of their disease, such that progression can be modified in this high-risk group of children and adolescents. A review of the pediatric literature will include a focus on the epidemiology, risk factors, pathology, screening, and treatment of kidney disease in youth onset T2DM.